KINERJA RANTAI PASOK DAN NILAI TAMBAH DENGAN INTERNALISASI ASPEK LINGKUNGAN PADA AGROINDUSTRI AYAM RAS PEDAGING - Nurhayati, Marimin, Taufik Djatna, Idat G Permana (Jurnal Teknologi Industri Pertanian, 2016)
Environment aspects become very important in measuring the performance of supply chain as well asmeasuring value added of poultry industry. This research aimed at proposing a green supply chain performanceand green value added on agroindustry of poultry supply chain. LCA approach was used in structuring greensupply chain performance measurement. Green value added in the poultry supply chain was measured byconsidering not only financial perspectives but also environmental aspects. The study showed that greenperformance of supply chain with functional unit 20.000 head of chicken. impact resulted from farm:acidification (17.100 M2UES), eutrophication (58.400 M2UES), global warming (91.300 kgCO2Eq) andecotoxicity (291.000 kg TEG-Eq); for slaughter unit: acidification (12.400 M2UES), eutrophication (42 200M2UES), global warming (66.000 kgCO2Eq) and ecotoxicity (210.000 kg TEG-eq); for processing unit:acidification (7.410 M2UES), eutrophication (25.000M2UES), global warming (39.900 KgCO2Eq), andecotoxicity (124.000 kg TEG-Eq). Second, green value added of farmer, slaughter house, and processing unitwere IDR65,837,800; IDR10,034,500;and IDR 30,608,600,respectively.Keywords: green supply chain, performance measurement, poultry, LCA, green value added